2017
DOI: 10.1109/comst.2017.2657881
|View full text |Cite
|
Sign up to set email alerts
|

Void-Handling Techniques for Routing Protocols in Underwater Sensor Networks: Survey and Challenges

Abstract: From the view of routing protocols in Underwater Sensor Networks (UWSNs), the presence of communication void, where the packet cannot be forwarded further using the greedy mode is perhaps the most challenging issue. In this paper, we review the state of the art of void-handling techniques proposed by underwater routing protocols. To this, we first review the void problem and its negative impact on the category of the routing protocols, which does not entail any void recovery technique. Afterwards, currently av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(67 citation statements)
references
References 113 publications
(188 reference statements)
0
67
0
Order By: Relevance
“…Several studies have already been carried out for efficient routing protocols in UWSNs [12][13][14]; however, we describe the closely related work in this section, i.e., all those protocols that depend on the pipeline radius for directionality purposes using a node's relative coordinates [15] and timer information [16] for broadcasting.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have already been carried out for efficient routing protocols in UWSNs [12][13][14]; however, we describe the closely related work in this section, i.e., all those protocols that depend on the pipeline radius for directionality purposes using a node's relative coordinates [15] and timer information [16] for broadcasting.…”
Section: Related Workmentioning
confidence: 99%
“…The geographic routing schemes have been shown to be very suitable for UWSNs, because they do not need the communication overhead to discover and maintain the full path from the source to the destination. However, the characteristics of underwater environments make it more difficult for such schemes to cope with void regions [27]. Mainly because the void regions are 3D, which require special treatments than 2D voids in terrestrial networks; and because sensor nodes mobility in underwater creates mobile void regions.…”
Section: The Grid Void Avoidance (Gva) Scheme Of Va-gmprmentioning
confidence: 99%
“…Underwater sensor networks (UWSNs) are widely used to support aquatic applications such as environmental monitoring, exploration of ocean resource, early warning systems, and seismic and volcanic prediction. Underwater sensor nodes are deployed in different depths of the region of interest to collect aquatic information and forward them to any one of the sinks on the surface [1][2][3]. Sink nodes then deliver the accumulated information to the monitoring centre via the terrestrial radio links for further analysis, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…If such, the packet is dropped even though there is a valid path from the sender to the destination. This phenomenon is called the communication void or local maximum [1,8]. Different factors such as permanent or temporary obstacles, sparse topology, shadow zones, and unreliable nodes or links are considered as the most common reasons for this phenomenon happening [1].…”
Section: Introductionmentioning
confidence: 99%